Analisis Model Pendukung Keputusan Simple Additive Weighting (SAW) terhadap Top 10 Traveler Ranked Hotel - Yerik Afrianto Singgalen (STMIK Budi Darma, 2023)
The decision support model is essential in helping passengers choose which tourist attractions and lodging facilities to use. However, creating systems for prioritizing institutional programs remains the sole focus of research into decision-support models.Considering this, this study offers ideas to analyze the Simple Additive Weighting (SAW) decision support model as a support for hotel stay decisions based on data from the top 10 traveler-ranked hotels in Makassar City as follows: Claro Makassar; The Rinra Makassar, Swiss-Belhotel Makassar; Novotel Makassar Grand Shayla; Almadera Hotel; Dalton Hotel Makassar; MaxOneHotels @Resort Makassar; Ibis Makassar City Center; Harper Perintis-Makassar; Aryaduta Makassar. The criteria set out in this study are divided into two parts: standards based on the availability of room rooms (property amenities, room features, and room types) and hotel guest ratings (location, cleanliness, services, value). The categories and weights of values based on room availability are as follows: property amenities are categorized as the cost with a weight of 0.50; Room feature is ranked as the cost with a weight of 0.25; room type is classified as the cost with a weight of 0.25. In addition, the categories and weights of values based on guest ratings are as follows: location is categorized as benefit with a weight of 0.20; cleanliness is categorized benefit with a weight of 0.25; Service is categorized benefit with a weight of 0.30, and value is classified as cost with a weight of 0.25. The results of this study show that the ranking can be categorized into two, namely, based on room availability and hotel guest ratings. Based on room availability criteria (property amenities, room features, and room type), Novotel Makassar Grand Shayla ranks first with a total value of 0.85, and Ibis Makassar City Center Hotel ranks second with a total value of 0.75. Based on the assessment of hotel guest rating criteria (location, cleanliness, services, value), Arya Duta Hotel ranks first with a total value of 0.94, and Almadera Hotel ranks second with a total value of 0.88. Thus, accommodation services can be recommended to guests based on room availability (property amenities, room features, and room type) or guest ratings (location, cleanliness, services, value) in the top 10 traveler-ranked hotels in Makassar City.